Establishment, Growth Performance and Some Aspects of Ecophysical Characteristics of Two Rattan Species: Calamus Manan and Calamus Tumidus - Mohamad, Aminuddin (1987)
Rattans are indigenous spiny climbing palms and are considered to be the most important non-wood forest produce in Malaysia. In recent years, a tremendous increase in demand for rattans has outs tripped natural supply consequently initiating large scale plantings. Al though rattan research in Malaysia commenced in 1975, knowledge on its silviculture is still rudimentary. In this study, basic aspects of establishment, growth performance and ecophysiology of Calamus manan and C. tumidus, two of the more important indigenous species, will be elucidated as a basis to silvicultural application.